The humoral immune response of the lepidopteran model insect, silkworm Bombyx mori L., to microbial pathogens - Abrar Muhammad; Chao Sun; Yongqi Shao (Current Research in Insect Science)
Insects are valuable models for studying innate immunity and its role in combating infections. The silkworm Bombyx mori L., a well-studied insect model, is susceptible to a range of pathogens, including bacteria, fungi, viruses, and microsporidia. Their susceptibility makes it a suitable model for investigating host-pathogen interactions and immune responses against infections and diseases. This review focuses on the humoral immune response and the production of antimicrobial peptides (AMPs), the phenoloxidase (PO) system, and other soluble factors that constitute the primary defense of silkworms against microbial pathogens. The innate immune system of silkworms relies on pattern recognition receptors (PRRs) to recognize pathogen-associated molecular patterns (PAMPs), which then activate various immune pathways including Imd, Toll, JAK/STAT, and RNA interference (RNAi). Their activation triggers the secretion of AMPs, enzymatic defenses (lysozyme and PO), and the generation of reactive oxygen species (ROS). Collectively, these pathways work together to neutralize and eliminate pathogens, thereby contributing to the defense mechanism of silkworms. Understanding the innate immunity of silkworms can uncover conserved molecular pathways and key immune components shared between insects and vertebrates. Additionally, it can provide valuable insights for improving sericulture practices, developing strategies to control diseases affecting silk production, and providing a theoretical foundation for developing pest control measures.